KEBIJAKAN DAN PENGAMBILAN KEPUTUSAN DALAM LEMBAGA PENDIDIKAN ISLAM - Sabri, Ahmad (AT-TALIM, 2013)
Human beings as individuals and social beings are constantly faced with various problems or issues that they encounter in almost every side of life.Â  Precise decision making is required to overcome these problems so that all of the alternative solutions can be achieved optimally.Â  Oneâs position in an organization or institution has often been distracted by some polices and decision, and therefore, he or she has to consider solutions while keeping the organization runs well.Â Â  This is so because in every organization whether big and small, the changing of situationÂ  such as personnel shiftÂ  has often raised conflict and misunderstanding.Â  These problems must be avoided or clarified.Â  Policy and decision making in substantive Islamic education is not too much different from the common theories of policy and decision-making. However, the policy and decision-making in Islamic education is more focused on the principles outlined in the Quran and the Hadith of the Prophet (Peace be upon him).Â CopyrightÂ Â©Â 2013 by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v20i2.34